123k views
2 votes
7+4(r+3)=9r-6
show work pls AND HELP ASAP

User Matt Lacey
by
5.6k points

1 Answer

2 votes


\: \: \: \: \: \:


= \: \: \: \: r = 5

Explanation:


7 + 4(r + 3) = 9r - 6

  • distribute 4 through the parentheses


7 + 4r + 12 = 9r - 6

  • add numbers


19 + 4r = 9r - 6

  • move the variable to the left hand side and change its sign


19 + 9r = - 6

  • move the constant to the right hand side and change its sign


4r - 9 = - 6 - 19

  • collect like terms


- 5r = - 6 - 19

  • calculate the difference


- 5r = - 25

  • divide both sides of the equation by -5


= \: \: \: \: r = 5

hope it helps

User Max Hampton
by
5.0k points